2000
DOI: 10.1603/0022-0493-93.2.240
|View full text |Cite
|
Sign up to set email alerts
|

Phenology and Spatial Pattern ofTyphaea stercorea(Coleoptera: Mycetophagidae) Infesting Stored Grain: Estimation by Pitfall Trapping

Abstract: The hairy fungus beetle, Typhaea stercorea (L.), occurs frequently in stored grain, often in large numbers. Populations infesting stored barley in Minnesota, corn in South Carolina, and wheat in Florida were sampled by means of grain probe traps. Spatial distribution of the species was examined by contour analysis of trap catch. In South Carolina, corn was sampled at 2 locations over 2 storage seasons, and temperature, moisture content, and malathion residues were measured. These data were used to examine phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 11 publications
0
2
0
2
Order By: Relevance
“…Grain temperature and temperature in the head space of the bins were measured and recorded by means of TP10 thermistor probes and an Easy Logger Field Unit (Model FA-110, Omnidata, Logan, UT) as described by Arbogast et al (2000). Temperature was measured every 10 min, and hourly averages were recorded on a data storage module (Omnidata DSM 100) for later downloading to computer storage.…”
Section: Measurement and Analysis Of Temperature And Grain Moisture Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Grain temperature and temperature in the head space of the bins were measured and recorded by means of TP10 thermistor probes and an Easy Logger Field Unit (Model FA-110, Omnidata, Logan, UT) as described by Arbogast et al (2000). Temperature was measured every 10 min, and hourly averages were recorded on a data storage module (Omnidata DSM 100) for later downloading to computer storage.…”
Section: Measurement and Analysis Of Temperature And Grain Moisture Cmentioning
confidence: 99%
“…Furthermore, data reported by Arbogast et al (2000) showed that malathion residues on farm-stored corn in South Carolina decline exponentially throughout the storage season. Thus, maximum growth of the moth populations occurred when malathion levels were at their highest.…”
Section: Article In Pressmentioning
confidence: 99%
“…Para cada grupo de organismo, utiliza-se de um método diferente de captura ao qual se enquadre melhor na atratividade do grupo desejado (Almeida et al, 1998). Armadilhas de queda, por exemplo, são amplamente utilizadas para coleta passiva de animais terrestres, tais como Isoposa (Paoletti & Hassall, 1999;Hornung et al, 2007), Diplopoda (Kime, 1997;Snyder et al, 2006), Chilopoda (Adis, 1992;Shear & Peck, 1992;Voigtlander, 2003), Araneae (Koponen, 1992;Bauchhenss, 1995;Buddle, et al, 2000) e Coleoptera (Epstein & Kulman, 1990;Simmons et al, 1998;Arbogast et al, 2000;Martínez et al, 2009;Anlas et al, 2011;Thakare et al, 2011;Costa-Silva et al, 2014), além de anfíbios, répteis e até pequenos mamíferos (e.g. Semlitsch et al, 1981;Mengak & Guynn, 1987;Williams & Braun, 1983;Ellis, 2013).…”
Section: Armadilha De Quedaunclassified
“…Armadilhas de queda, citadas pela primeira vez há mais de 110 anos (Dahl, 1896), foram desenvolvidas para a coleta de insetos cujos hábitos de forrageamento se caracterizam pelo deslocamento contínuo sobre o solo à procura de recursos alimentares (Danchin et al, 2008). Têm sido frequentemente empregadas para coleta passiva de insetos terrestres, mais comumente formigas e besouros, além de outros artrópodes tais como aranhas (Bestelmeyer et al, 2000;Southwood & Henderson, 2000;Arbogast et al, 2000;. Ao longo de décadas, diferentes tipos de materiais foram empregados para confecção deste tipo de armadilha, dentre os quais o metal , o vidro e o plástico .…”
Section: Introductionunclassified